The chronic mountain sickness - Monge, Carlos (1943)
When a subject is going to match, you must first adapt to a condition of permanent anoxia, using its emergency mechanisms to achieve later with a new type of biological balance, balanced state of homeostasis of the Andean people. Consequently, the adaptive period is therefore a disease: Mountain Sickness, which may be inapparent, acute, subacute or chronic.